Nilai Dalam Legenda Mamuli Pada Masyarakat Kampung Praijing, Desa Tebara, Kota Waikabubak, Kabupaten Sumba Barat - Renia Linda Bulu; Sanhedri Boimau; Richard Oematan (Kampus Akademik Publiser, 2026)
The issue raised in this study is what values are contained in the legend of Mamuli among the people of Praijing Village, Waikabubak City, West Sumba Regency. The benefits of this study are: contributing to the development of studies in the anthropology of oral literature and cultural studies, particularly regarding values and legends in Sumbanese society; adding academic references on the values contained in the Mamuli legend; and serving as a foundation for subsequent researchers. The aim of the study is to describe the values contained in the Mamuli among the people of Praijing Village, Tebara Subdistrict, Waikabubak City, West Sumba Regency. The theory used in this study is the theory of Literary Anthropology. The method used in this study is the qualitative descriptive method. The results of the study show that the values of Mamuli among the people of Praijing Village, Tebara Subdistrict, Waikabubak City, West Sumba Regency are (1) Historical Value; in the Mamuli among the people of Praijing Village, Tebara Subdistrict, Waikabubak City, West Sumba Regency, this is reflected in the existence of Mamuli as a cultural heritage of the ancestors that has existed since ancient times and has been passed down from generation to generation. (2) Religious Value; in the Mamuli among the people of Praijing Village, Tebara Subdistrict, Waikabubak City, West Sumba Regency, this is evident from the community's belief that Mamuli holds values related to life, fertility, and respect for ancestors. (3) Cultural Value; in the Mamuli, this reflects the identity of the Sumbanese people as a community that upholds customs, beliefs (marapu), as well as the relationship between humans, ancestors, and nature. (4) Social Value in the form of respect for women; the Mamuli is a symbol that affirms the high regard of Sumbanese society for women. Keywords: Value; Legend; Mamuli.